2018
DOI: 10.3758/s13423-018-1468-z
|View full text |Cite
|
Sign up to set email alerts
|

When does reading dirty words impede picture processing? Taboo interference with verbal and manual responses

Abstract: Picture naming takes longer in the presence of socially inappropriate (taboo) distractor words compared with neutral distractor words. Previous studies have attributed this taboo interference effect to increased attentional capture by taboo words or verbal self-monitoring-that is, control processes scrutinizing verbal responses before articulation. In this study, we investigated the cause and locus of the taboo interference effect by contrasting three tasks that used the same target pictures, but systematicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 15 publications
0
4
0
Order By: Relevance
“…Consistently, lexical decision experiments have reported detrimental effects of the taboo connotation on reaction times (e.g., Carretié et al, 2008; Sulpizio et al, 2019; Sulpizio, Pennucci, et al, 2020). Taboo words have also been found to yield an increased interference compared to nontaboo ones when used as distractors within picture–word interference (Hansen et al, 2017; Mädebach et al, 2018; White et al, 2016; White et al, 2017) and Stroop paradigms (MacKay et al, 2004; Siegrist, 1995). Taken together, these findings seem to point toward a pervasive influence of taboo words irrespective of their status as targets or distractors within different experimental paradigms.…”
mentioning
confidence: 99%
“…Consistently, lexical decision experiments have reported detrimental effects of the taboo connotation on reaction times (e.g., Carretié et al, 2008; Sulpizio et al, 2019; Sulpizio, Pennucci, et al, 2020). Taboo words have also been found to yield an increased interference compared to nontaboo ones when used as distractors within picture–word interference (Hansen et al, 2017; Mädebach et al, 2018; White et al, 2016; White et al, 2017) and Stroop paradigms (MacKay et al, 2004; Siegrist, 1995). Taken together, these findings seem to point toward a pervasive influence of taboo words irrespective of their status as targets or distractors within different experimental paradigms.…”
mentioning
confidence: 99%
“…Taboo language has been increasingly used to investigate the impact of strong emotion on language processing, with results suggesting that distractor taboo words reliably lead to interference in picture naming tasks (Madan et al, 2017; Mädebach et al, 2018; White & Abrams, 2021; White et al, 2016, 2017) and taboo Stroop tasks (MacKay et al, 2004; Scaltritti et al, 2022). The consensus of these studies is that tabooness affects early stages of lexical processing via arousal-induced attentional capture (Hansen et al, 2017; MacKay et al, 2004; Mathewson et al, 2008), which can persist beyond a single trial (White & Abrams, 2021).…”
Section: Processing Of Strongly Arousing Language In Young and Older ...mentioning
confidence: 99%
“…Motivated by the publication of our study, Mädebach, Markuske and Jescheniak (2018) recently found that taboo distractors not only interfere with picture naming but also impede manual responses for phoneme decisions and natural size judgements. Thus, it seems taboo interference is best characterised as a pre-lexical, conceptual level effect and appears to be relatively independent of the speech production system.…”
Section: Distraction and Monitoring In Taboo Language Processingmentioning
confidence: 90%
“…However, this distractor-based attention-capture/blocking mechanism could be relatively independent of the production system, i.e., it could be engaged irrespective of the nature of the primary task. For example, a recent study by Mädebach, Markuske and Jescheniak (2018) found that taboo distractors not only interfere with picture naming but also impede manual responses for phoneme decisions and natural size judgements about depicted objects. If so, then dorsolateral PFC, IFG and ACC (dorsal subdivision) might be engaged (see Song et al, 2017).…”
Section: Introductionmentioning
confidence: 99%